2012
DOI: 10.1111/j.1943-278x.2012.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Suicidal Ideation among Depressed Women with Childhood Sexual Abuse Histories

Abstract: Depressed women with sexual abuse histories have a heightened risk of suicidal ideation (SI), which may be only in part attributable to psychiatric symptoms of depression and posttraumatic stress disorder (PTSD). Emotions and SI were studied among 106 women with histories of childhood sexual abuse enrolled in treatment trials for major depression. Assessments were conducted at baseline, 10, 24, and 36 weeks. Sadness, guilt, and shame-proneness were associated with self-reported and observer-rated SI across tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 55 publications
1
31
1
2
Order By: Relevance
“…Although we did not find evidence to support our second hypothesis – that women with childhood sexual abuse would have greater distress and suicidality – we found that a nuanced relationship exists between self‐conscious emotions and suicidal thoughts. Whereas other research has found both guilt and shame to be associated with suicidal ideation among women with sexual trauma histories (You et al., ), we found that a history of childhood sexual abuse moderates the relationship between self‐conscious emotions and suicidal ideation. Specifically, after controlling for the effects of depressive symptoms, guilt was associated with the frequency of suicidal thoughts amongst women without childhood sexual trauma, while shame was associated with frequency of suicidal thoughts amongst women who reported a history of childhood sexual abuse.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although we did not find evidence to support our second hypothesis – that women with childhood sexual abuse would have greater distress and suicidality – we found that a nuanced relationship exists between self‐conscious emotions and suicidal thoughts. Whereas other research has found both guilt and shame to be associated with suicidal ideation among women with sexual trauma histories (You et al., ), we found that a history of childhood sexual abuse moderates the relationship between self‐conscious emotions and suicidal ideation. Specifically, after controlling for the effects of depressive symptoms, guilt was associated with the frequency of suicidal thoughts amongst women without childhood sexual trauma, while shame was associated with frequency of suicidal thoughts amongst women who reported a history of childhood sexual abuse.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings from the present study contribute further to the evidence base linking self‐conscious emotions with suicidality (Bryan et al., ; Weingarden et al., ; You et al., ). Our findings, however, also highlight the importance of developing a better understanding of the nuanced relationship between shame, guilt and suicidal ideation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The quantitative studies demonstrate the centrality of shame, finding the presence of shame mediated a range of psychological outcomes, including the effectiveness of group psychotherapy on reducing PTSD symptoms (Ginzburg et al, ), sexual revictimisation in adulthood (Kessler & Bieschke, ) and body surveillance and alexithymia (Watson, Matheny, Gagné, Brack, & Ancis, ). Additionally, associations, were found between: shame and suicidal ideation (Kealy, Spidel, & Ogrodniczuk, ; Milligan & Andrews, ; You, Talbot, He, & Conner, ), self‐harming behaviours (Milligan & Andrews, ), dissociation (Talbot, Talbot, & Tu, ), body related trauma (Dyer, Feldman, & Borgmann, ), poor mental health (Rahm, Renck, & Ringsberg, ) and anxiety and depressive symptoms (Willie et al, ). CSA‐related shame also significantly correlated with HIV‐related shame (Willie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recently emerging body of literature includes psychiatric studies linking shame and suicide (Wiklander et al 2012;Bryan et al 2013;Anderson, Sisask, and Varnik 2011;You et al 2012), a qualitative investigation of patients who had attempted suicide that included evidence of feelings of shame (Vatne and Nåden 2012) and studies that demonstrate that the experience of shame is implicated in queer youth suicide (Cover 2012;McDermott, Roen, and Scourfield 2008). This body of literature constitutes a framework that renders shame visible in relation to suicide.…”
Section: The Cultural Politics Of Shame and Suicidementioning
confidence: 97%